N-acetylcysteine for prevention of radiocontrast induced nephrotoxicity: the importance of dose and route of administration. Issue 8 (14th July 2005) - Shalansky, S J; Pate, G E; Levin, A; Webb, J G
Abstract : Dose and route of administration of N-acetylcysteine are key factors to consider when evaluating whether this agent is effective in preventing radiocontrast induced nephropathy